Evolution of earth pressure coefficient of sand undergoing varying rate of dissolution. Issue 1 (31st March 2022) - Viswanath, P.; Das, A.; Buscarnera, G.
Abstract : In fluid-saturated granular materials, the physicochemical interaction between pore-fluids and grain minerals alters packing conditions, which in turn leads to stress change, deformation and, in extreme cases, even collapse. Chemical weathering, either naturally occurring or induced by human activities, is among such processes. This paper presents an experimental study illustrating the major effects of chemical weathering on the deformation and stress state of granular materials, emphasising particulate systems entirely made by highly soluble carbonate grains. Laboratory experiments are conducted by subjecting granular assemblies to acidic environments under oedometric conditions. The reaction rate is controlled by regulating various testing parameters, such as acid concentration and pore fluid flow rate. Experiments revealed that the lateral earth pressure steadily reduces in some cases, while others exhibit non-monotonic evolution. From a macroscopic standpoint, the rate of the chemical reaction was critical to determine the emergence of either of these trends. Such findings are relevant for any particulate system in which the stress conditions are controlled by multi-physical processes proceeding at different rates, such as waste products within bioreactors, gouge materials within faults and natural deposits subjected to the injection/extraction of reactive fluids.